A PAGE screening approach for identifying CRISPR-Cas9-induced mutations in zebrafish. (2018) - VanLeuven, Ariel J; Park, Sungdae; Menke, Douglas B; Lauderdale, James D
The introduction of CRISPR-Cas9 technology for targeted mutagenesis has revolutionized reverse genetics and made genome editing a realistic option in many model organisms. One of the difficulties with this technique is screening for mutations in large numbers of samples. Many screening approaches for identifying CRISPR-Cas9 mutants have been published; however, in practice these methods are time consuming, expensive, or often yield false positives. This report describes a PCR-based screening approach using non-denaturing PAGE. This approach does not depend on the formation of heteroduplexes and reliably detects changes as small as 1 base-pair (bp) in nucleic acid length at the target site. This approach can be used to identify novel mutations and is also useful as a routine genotyping method.